Intestinal Tuberculosis Presenting with Gastrointestinal Bleeding in Patient on Warfarin Therapy - Werimo Pascal Kuka; Joe Rakiro; Joseph Gatheru; Felix Riunga; Allan Rajula (Case Reports in Gastrointestinal Medicine)
Background. Intestinal tuberculosis (ITB) constitutes less than 5% of overall cases of extrapulmonary disease and mostly affects the ileocecal region. The presentation and radiologic findings in enteric tuberculosis can mimic Crohn’s disease (CD). Case Presentation. We present a case report of an African woman who presented to a Kenyan hospital with lower gastrointestinal bleeding while on anticoagulation for valvular atrial fibrillation, and was diagnosed with intestinal tuberculosis after colonoscopy, biopsy, and positive staining for tuberculous bacilli. Conclusion. Intestinal tuberculosis causing gastrointestinal bleeding is rare but should be suspected in patients living in TB endemic regions.